2019. Host Gene Expression Signatures for Diagnosis of Acute Respiratory Infections in the Elderly. (26th November 2018) - Bloom, Allison; Suchindran, Sunil; Mazur, Anna; Mcclain, Micah T
Abstract: Background: Despite advances in molecular techniques the etiology of acute respiratory infections (ARIs) is often difficult to differentiate either at the point of care or with advanced microbiological techniques. There is growing interest in host biomarker assays, including those based on gene expression patterns in circulating cells, to aid in differentiation of viral and bacterial diseases. However, there are concerns about how such tests perform in vulnerable aging populations where host responses are often muted. Methods: In order to assess performance of gene expression-based biomarkers, we enrolled patients presenting to the emergency department with clinical ARI and selected 184 individuals aged ≤25 and ≥60 years old with proven viral or bacterial ARI. Gene expression in peripheral blood was measured with Affymetrix microarrays. Published viral and bacterial signatures were applied to the data and Bayesian approaches were used to develop novel discriminative models. Results: We noted a marked decline in signature performance between younger and older individuals in both viral (AUC 0.90 vs. 0.64) and bacterial (AUC 0.91 vs. 0.50) infections. Incorporation of age-related genomic changes was able to restore much of the signature performance in older individuals. When examining the genomic differences driving the drop in signature performance, we found marked perturbations in expression of immunoglobulin genes and pathways driving known immunoregulatory mechanisms that provide novel insights into an age-related decline in ARI-focused immunity. Conclusion: Pathogen class-specific host-based gene expression signatures offer great promise as diagnostic tools. However, altered immune responses in vulnerable populations such as the elderly are also manifested at the genomic level and can affect diagnostic signature performance. Age-specific alterations in the components of a diagnostic signature can minimize much of this effect, however this work highlights the need for consideration of age during biomarker development for infectious diseases. Furthermore, studies of age-related differences in biomarker performance can lead to important breakthroughs in our understanding of age-associated alterations in immunity. Disclosures: All authors: No reported disclosures.